The Role of Human Resource Management in Developing the Human Capital for Global Excellence-An Empirical Study (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Companies currently are facing various crucial business challenges; Intellectual capital, Technology, Globalization, Profitability through growth, and Change. These challenges require organizations to build new capabilities in a collaborative manner, and it is human resource management developing these capabilities. It enables the organizations by playing the leadership role in meeting competitive challenges. HR professionals have shed their traditional image of policing rule making policy. Today HR professionals are held responsible for the employee’s engagement and commitment towards the organization and making them contribute and stepping into the shoes of ownership. It is no longer administrative dinosaur. It has changed from a narrow picture, reactive role to a much wider canvas. By bringing the management of the organization together with the employees, a new management of human resources triggers, a merging of the reservoir of knowledge of the person and the organization, culminating in the combined triumph of both. Competitiveness at the global level can be achieved not by only using the upgraded technologies and facilities, but by motivating employees efficiently and effectively, to comply with universal standards. Every company on the world stage, human resources professionals have the mission to affect the business world; HR is now on a paradigm shift and as a support function, withered on the board, called on to help others and to  hire and fire from the companies are rapidly eroding. Human resources playing a very proactive role in managing the problems of globalization. It brings change and improves the individuals' ability to learn and collaborate, manage diversity, ambiguity and complexity. The research is an attempt to understand the role of HRM in building national talent for global achievement and to study and compare the perception of corporate employees, management faculties & management students.